Computed tomography-based deep-learning prediction of lymph node metastasis risk in locally advanced gastric cancer - Zhang, An-qi; Zhao, Hui-ping; Li, Fei; Liang, Pan; Gao, Jian-bo; Cheng, Ming (Frontiers in Oncology, 2022)
Purpose: Preoperative evaluation of lymph node metastasis (LNM) is the basis of personalized treatment of locally advanced gastric cancer (LAGC). We aim to develop and evaluate CT-based model using deep learning features to preoperatively predict LNM in LAGC. Methods: A combined size of 523 patients who had pathologically confirmed LAGC were retrospectively collected between August 2012 and July 2019 from our hospital. Five pre-trained convolutional neural networks were exploited to extract deep learning features from pretreatment CT images. And, the support vector machine (SVM) was employed as the classifier. We assessed the performance using the area under the receiver operating characteristics curve (AUC) and selected an optimal model, which was compared with a radiomics model developed from the training cohort. A clinical model was built with clinical factors only for baseline comparison. Results: The optimal model with features extracted from ResNet yielded better performance with AUC of 0.796 [95\% confidence interval (95\% CI), 0.715-0.865] and accuracy of 75.2\% (95\% CI, 67.2\%-81.5\%) in the testing cohort, compared with 0.704 (0.625-0.783) and 61.8\% (54.5\%-69.9\%) for the radiomics model. The predictive performance of all the radiological models were significantly better than the clinical model.